Mesenchymal gene expression subtyping analysis for early-stage human papillomavirus-negative head and neck squamous cell carcinoma reveals prognostic and predictive applications - Mayhew, Gregory M.; Uronis, Joshua M.; Hayes, David Neil; Zevallos, Jose P. (Frontiers in Oncology, 2022)
Patients with oral cavity squamous cell carcinoma (OCSCC) are predominantly HPV(-) and treatment typically involves surgical resection +/- neck dissection, followed by radiation +/- chemotherapy. We previously described four mRNA expression patterns (classical, atypical, basal, and mesenchymal), each with unique genomic features and prognosis. Here, we examine the clinical utility of gene expression subtyping in HNSCC and introduce potentially predictive applications in HPV(-) OCSCC. A retrospective genomic database analysis was performed including 562 HNSCC patients from MD Anderson (MDA-GSE41116) and The Cancer Genome Atlas (TCGA). Samples were assigned molecular subtypes (Classical, Atypical, Basal, and Mesenchymal) using an 88-gene classifier. HPV status was determined by gene expression. The clinical endpoint was overall survival censured at 36 months. Kaplan-Meier plots and logrank tests were used to investigate associations between clinical variables and survival. Of the 418 TCGA training patients that met analysis criteria, nearly 20% presented as stage I/II. Among node(-) OCSCC patients, the Mesenchymal subtype associated with worse survival (HR 2.4, p=0.021), offering a potentially actionable biomarker in otherwise early-stage, low-risk disease. This was confirmed in the MDA validation cohort. Node(-) non-Mesenchymal OCSCC patients had far better survival compared to node(-) Mesenchymal and all node(+) patients which had similarly poor survival. These findings suggest that the Mesenchymal subtype is associated with poor survival in surgically-resected, early-stage, node(-) OCSCC otherwise expected to have favorable outcomes. These findings highlight the potential value of gene expression subtyping as a pathology adjunct for prognostication and treatment decision-making in OCSCC patients.